2022
DOI: 10.1037/per0000539
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and construct validity of the general factor of personality disorder.

Abstract: Criterion B of the alternative model of personality disorder in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), outlines maladaptive trait dimensions that characterize personality disorders. Emerging evidence from bifactor confirmatory factor analyses suggest these traits are related at a higher order level by a general factor of personality disorder (g-PD). Further, emerging evidence points to traits most closely related to borderline personality disorder as underpinnings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
(112 reference statements)
1
5
0
Order By: Relevance
“…Additionally, other published studies found that bipolar disorder/mania symptoms loaded on either the psychosis or internalizing dimensions, with borderline PD and major depressive disorders equally fitting in this latter dimension, reflecting an affective dysregulation foundation [33,[40][41][42][43][44]. It can be argued that these data also feature psychoticism as a core trait domain posits as a general factor of personality disorder [45][46][47], or as a core personality dysfunction [48]. In this follow-up, there is evidence that psychoticism can capture clinically relevant aspects of severe mental illness associated with psychosis and other related characteristics, indicating possibly shared patterns of personality expression [14,49], demonstrating a degree of non-specificity in the patterns across symptoms of personality disorders and non-personality disorders, similarly to some other evidence in the literature [49].…”
Section: General and Common Main Findings Of Borderline Pd And Bipola...mentioning
confidence: 86%
“…Additionally, other published studies found that bipolar disorder/mania symptoms loaded on either the psychosis or internalizing dimensions, with borderline PD and major depressive disorders equally fitting in this latter dimension, reflecting an affective dysregulation foundation [33,[40][41][42][43][44]. It can be argued that these data also feature psychoticism as a core trait domain posits as a general factor of personality disorder [45][46][47], or as a core personality dysfunction [48]. In this follow-up, there is evidence that psychoticism can capture clinically relevant aspects of severe mental illness associated with psychosis and other related characteristics, indicating possibly shared patterns of personality expression [14,49], demonstrating a degree of non-specificity in the patterns across symptoms of personality disorders and non-personality disorders, similarly to some other evidence in the literature [49].…”
Section: General and Common Main Findings Of Borderline Pd And Bipola...mentioning
confidence: 86%
“…Finally, we examined measurement invariance within the PID-5-BF in the context of a correlated factors model, which is empirically consistent with the original hypothesized structure of the PID-5-BF. Emerging evidence suggests higher order, and bifactor models also show good fit for PID-5 brief forms (e.g., Asadi et al, 2022; Bagby et al, 2022; Gomez et al, 2020; Hyatt et al, 2021), and future investigations should continue to examine the invariance of higher order dimensions of the PID-5 brief forms as well.…”
Section: Discussionmentioning
confidence: 99%
“…toward a dimensional approach that focuses more on the degree of impairment in self and interpersonal functioning. 4,5 Readiness for change needs to be distinguished from readiness for treatment, which are related but different ideas. Readiness for change means a patient is prepared to alter a particular pattern of behavior in a general sense, typically with awareness and acknowledgement that the pattern is leading to distress or impairment.…”
Section: Introductionmentioning
confidence: 99%
“…We also highlight how the personality disorder literature is moving away from a purely descriptive nosology of distinct entities (e.g., BPD, ASPD, OCPD, etc.) toward a dimensional approach that focuses more on the degree of impairment in self and interpersonal functioning 4,5 …”
Section: Introductionmentioning
confidence: 99%